1990
DOI: 10.1111/myc.1990.33.5.253
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Candida albicans on the stratum corneum of diabetic and non‐diabetic patients

Abstract: We have used a novel approach to in vitro culture of Candida albicans on cyanoacrylate skin surface strippings. It appears that with this model yeasts and hyphae grew on large surfaces of stratum corneum. The area of extension of the fungal growth was larger on stratum corneum taken from diabetic than from non-diabetic volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…5,12 Rurangirwa et al suggested that the inner face of the superficial layers of the stratum corneum of diabetics could be more prone to Candida invasion than that of non-diabetics. 13 In diabetic patients with vulvovaginal candidosis blood glucose level should be controlled in order to prevent future outbreakes of infection. 14 High concentration of glucose, arabinose and rybose in diet, enhances oral carriage, since Candida cells absorbs carbon from these sugars.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 Rurangirwa et al suggested that the inner face of the superficial layers of the stratum corneum of diabetics could be more prone to Candida invasion than that of non-diabetics. 13 In diabetic patients with vulvovaginal candidosis blood glucose level should be controlled in order to prevent future outbreakes of infection. 14 High concentration of glucose, arabinose and rybose in diet, enhances oral carriage, since Candida cells absorbs carbon from these sugars.…”
Section: Discussionmentioning
confidence: 99%
“…We have not explored in depth such findings which could indicate an indi vidual susceptibility of the human stratum corneum to fungal infections. This was shown in the past for C. albicans in diabetic and non diabetic patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…The problem is even more difficult in the clin ical situation where diseases are obviously not standardized with regard to the strain and amount of the fungi, and to the inhibitory activity of the immune and nonimmune re sponses to the infectious agent. Experimental infections in volunteers do not eliminate the intervention of the host response which is [9,10], The aim of the present study is to improve on previous approaches made in our labora tory [10][11][12][13] to quantify the inhibition of fun gal growth on stratum corneum following standardized topical application of antifun gals commercially available in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…47 This may explain the significant vulvar findings found in some women with diabetes with VVC. Furthermore, Segal et al 48 reported that adhesion (attachment) of C albicans to vaginal epithelial cells is increased in patients with diabetes compared with controls without diabetes.…”
Section: Glucosementioning
confidence: 97%